2006
DOI: 10.1002/ppul.20375
|View full text |Cite
|
Sign up to set email alerts
|

Epstein‐Barr virus‐associated bronchial leiomyoma in a boy with cellular immunodeficiency

Abstract: Bronchial leiomyoma is a rare disease in children. Recently, the association of leiomyoma and HIV infection was reported. We describe a boy with a cellular immunodeficiency, who had endobronchial leiomyoma. The tumor cells were positive for Epstein-Barr virus-encoded RNA-1 (EBER-1) and Epstein-Barr virus-determined nuclear antigen-2, suggesting a role of Epstein-Barr virus in the pathogenesis of leiomyoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 18 publications
0
40
0
Order By: Relevance
“…EBV-positive smooth muscle tumours (SMT) are not specific for transplant patients but are associated with any patients on long-term immunosuppression. Similar tumours can manifest in patients who suffer from human immunodeficiency virus (HIV) infection (HIV-SMT) or congenital immunodeficiency syndromes (CI-SMT) [3,4,5,6,7,8,9,10,11]. Among HIV patients and patients with rare congenital defects, the exact frequency of tumour manifestation is not known, but is most likely <5%.…”
Section: Pathogenesis Risk Factors and Molecular Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…EBV-positive smooth muscle tumours (SMT) are not specific for transplant patients but are associated with any patients on long-term immunosuppression. Similar tumours can manifest in patients who suffer from human immunodeficiency virus (HIV) infection (HIV-SMT) or congenital immunodeficiency syndromes (CI-SMT) [3,4,5,6,7,8,9,10,11]. Among HIV patients and patients with rare congenital defects, the exact frequency of tumour manifestation is not known, but is most likely <5%.…”
Section: Pathogenesis Risk Factors and Molecular Pathologymentioning
confidence: 99%
“…There is no gender-specific risk increase regarding any of the three tumour types [2,3,4,5,6,7,8,9,10,11]. In transplant patients, the type of immunosuppressive drug, the transplant organ and the manifestation of PTLD are not associated with PTSMT manifestation [2].…”
Section: Pathogenesis Risk Factors and Molecular Pathologymentioning
confidence: 99%
“…7,[10][11][12]14,15 Congenital immunodeficiency, such as ataxia telangiectasia and T-cell deficiency, have been linked to EBV-SMT; however, these cases are extremely rare. [3][4][5] Our case demonstrates that a broader range of immunodeficiency syndromes may be associated with the development of EBV-SMTs and highlights the utility of immune defenses outside of the adaptive system. Adrenal gland involvement in EBV-SMTs is surprising given the limited smooth muscle present.…”
Section: Resultsmentioning
confidence: 99%
“…We speculate that the severe deficiency of NK cells in our patient, despite normal cytotoxic CD8 ϩ T cells, was sufficient to compromise the initial immune response, therefore contributing to the development of an EBV-SMT as seen in HIV, organ transplant, and congenital T-cell deficiency patients. [3][4][5][6][7][8]12 The NK cell deficiency appeared to be quantitative because the few cells present were phenotypically normal and low-level activity could be detected after IL-2 stimulation. It has been shown that EBV transformation can increase levels of indoleamine 2,3-dioxygenase in some cells, leading to down-modulation of NKG2D from NK cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation